2022
DOI: 10.1503/cjs.006721
|View full text |Cite
|
Sign up to set email alerts
|

Health care costs after total knee arthroplasty for satisfied and dissatisfied patients

Abstract: Health care costs after total knee arthroplasty for satisfied and dissatisfied patients Background: Evidence suggests that up to 21% of patients are dissatisfied after total knee arthroplasty (TKA), but the link between dissatisfaction and use of health care resources is unknown. The objective of this study was to compare costs after TKA between satisfied and dissatisfied patients.Methods: This was a secondary analysis of a randomized clinical trial among patients who underwent primary TKA at our institution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A recent study showed that approximately 21% of patients with recent TKA are dissatisfied with the therapy when it does not resolve knee pain and function. Dissatisfied patients incurred a mean cost of $21,156.18, and when the therapy is effective, and knee pain is reduced, increasing their satisfaction, the mean cost is downgraded to $13,453.84 [82]. VRBR has been shown to be effective in managing knee pain after TKA, showing high satisfaction and adherence to the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that approximately 21% of patients with recent TKA are dissatisfied with the therapy when it does not resolve knee pain and function. Dissatisfied patients incurred a mean cost of $21,156.18, and when the therapy is effective, and knee pain is reduced, increasing their satisfaction, the mean cost is downgraded to $13,453.84 [82]. VRBR has been shown to be effective in managing knee pain after TKA, showing high satisfaction and adherence to the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary analysis of a randomized clinical trial (RCT) evaluating health-care resource utilization up to 12 months after primary TKA, among dissatisfied and satisfied patients, showed that patients dissatisfied with their return to function incurred a mean cost of $19,007.70, compared with $13,523.83 for satisfied patients (p = 0.07). Although the cost difference was not significant, its magnitude deserves attention 2 . Data from the New Zealand Joint Registry indicated that patients undergoing TKA have a mortality rate 8% higher than that of the general population 3 .…”
Section: Economicsmentioning
confidence: 91%
“…While a variety of non-pharmacological and pharmacological treatments for knee OA are available, these conservative measures are often clinically ineffective with regards to pain and fail to modify the disease process [ 6 ]. While total knee arthroplasty (TKA) is the standard of care for individuals with severe knee OA, only 9%–33% of patients with severe knee OA are willing to consider TKA [ [7] , [8] , [9] ] and approximately 20% of patients who undergo TKA report dissatisfaction with the procedure [ 10 ] due to persistent pain mostly thought to be related to synovitis [ 11 , 12 ]. Thus, there is potential benefit to a large cadre of patients in enhancing the armamentarium of available minimally invasive procedures for knee OA.…”
Section: Introductionmentioning
confidence: 99%